Comparative Evaluation Of Physico-Morphological Attributes Of Semen Of Jafarabadi, Mehsana (Bubalus Bubalis) And Crossbred (Hf X Kankrej) (Bos Indicus) Bulls - Patel, J. B.; Dhami, A. J.; Patel , P. A. (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
Semen ejaculates (90) of 15 mature bulls, 5 each of Jafarabadi, Mehsana and Crossbred (HF x Kankrej, F1) breeds collected at weekly interval during autumn season were studied for HOS test and physico-morphological attributes of spermatozoa and their interrelationships. The mean ejaculate volume (ml), mass activity (score 0-5), individual sperm motility (%), sperm concentration (million/ml), live sperm (%), abnormal sperm (%) and HOS reactive sperm (%) in Jafarabadi buffalo bulls semen were 4.81 ± 0.21, 3.30 ± 0.08, 74.33 ± 0.75, 1466.80 ± 72.43, 84.93 ± 0.59, 10.67 ± 0.43 and 70.47 ± 0.54, respectively. The corresponding values for Mehsana buffalo bulls semen were 5.01 ± 0.23, 3.23 ± 0.12, 73.83 ± 0.67, 1307.43 ± 94.27, 82.47 ± 0.67, 10.83 ± 0.38 and 71.53 ± 0.89; and in HF x K Crossbred bulls semen 6.68 ± 0.31, 2.83 ± 0.09, 72.00 ± 0.51, 1094.80 ± 78.85, 79.60 ± 0.65, 12.87 ± 0.45 and 61.37 ± 0.69, respectively. The three breeds varied significantly (P < 0.01) in their seminal attributes. The ejaculate volume and abnormal sperm per cent were significantly (P
Keywords: Seminal attributes; HOS test; Comparative evaluation; Jafarabadi buffalo; Mehsana buffalo; HF x K crossbred bulls